Digital technologies and digital hygiene in measuring mathematical knowledge - Papp Gabriella; Пап Габріелла (II. Rákóczi Ferenc Kárpátaljai Magyar Egyetem, 2025)
Abstract. Nowadays, in the higher education context, digital transformation represents not merely a technical shift, but also a pedagogical paradigm shift. This holds particularly true for disciplines built upon abstract conceptual systems, such as mathematics education. Digital technologies fundamentally alter the process of knowledge transfer and acquisition. They enable the dynamic visualization of abstract mathematical structures, inquiry-based learning, and the deepening of conceptual understanding. Alongside these technological innovations, digital assessment (e-tests) is becoming an integral part of the educational process, which, through immediate, automated feedback, can accelerate student development and support formative assessment strategies. The focus of our present research is the synthesis of these two areas—digital technology and digital hygiene—examined through the development of custom-designed electronic assessment tests (etests) applied in higher mathematics education. The primary target population of the research consisted of pre-service teachers in the Secondary Education (Mathematics) and Secondary Education (Informatics) programs, who, as future educators, play a key role in the transmission of digital pedagogical culture. The specific goal of our research was to create a quasi-standardized and reliable e-test suitable for the longitudinal measurement of knowledge acquired in the topic of combinatorics. The measurement was carried out at the end of the semester in the form of a delayed post-test, thus examining the existence of durable, structured knowledge rather than short-term memory. The aim and task of our research was to develop a methodological framework through which reliable and valid digital tests, providing rapid feedback, can be created for measuring the mathematical knowledge level of students in higher education. The development of such tools is essential for aligning technical advancement with increased pedagogical effectiveness, ensuring that digital instruments genuinely support the deeper levels of mathematics acquisition.
Keywords: mathematics education; digital technologies; digital hygiene; e-test